Inhibition of Arbovirus Assembly by Cycloheximide - Friedman, Robert M. (1969)
Addition of cycloheximide (100 μg/ml) to cultures of chick cells infected with Semliki Forest virus (SFV) halted subsequent increase in virus titers. When added after 4 hr of infection, the drug had no effect on the rate of viral ribonucleic acid (RNA) synthesis, although marked inhibition of protein synthesis was seen. All of the previously identified forms of SFV RNA were seen in the drug-treated cells at higher concentrations than were present in untreated controls. The latter observation appeared to result from a failure to form viral “cores” or nucleocapsids in the cycloheximide-treated cells, resulting in sequestration of viral RNA intracellularly. The failure to form new virus cores was correlated with the failure of type II cytopathic vacuoles to appear in thin sections. Virus budding from the cell surface and the formation of type I cytopathic vacuoles persisted in cycloheximide-treated cells. The cellular pool of the major protein present in the virus core appeared to be small. None of this protein was found in a free pool in cytoplasm. The results indicated that, in the presence of cycloheximide, virus assembly was impaired because of the small size of the cellular pool of the major protein required for virus core formation.